A new species of the genus Mongolotettix Rehn, 1928 from Inner Mongolia, China (Acrididae, Acridoidea, Orthoptera) - Shi, Jian-Ping; Dang, Yan; Yin, Zhan (Zootaxa, 2017)
The grasshopper genus Mongolotettix Rehn, 1928 is a median genus of family Acrididae. It contains 10 species that are distributed in Far Eastern Asian countries, including China, Japan, Korea, Mongolia, and Russia (Bolívar, 1898; Uvarov, 1914; Caudell, 1921; Bei-Bienko & Mishchenko, 1951; Chogsomzhav,1974; Li & Lian, 1994; Yin et al, 1996; Wan et al. 1998, Xie & Li 2000, Yin, Xia et al, 2003; Yin, Zhang et al, 2003; Yin et al, 2004; Kim & Kim, 2005; Huang et al, 2010; Shi et al. 2016; Storozhenko, 2016; Eades et al. 2017; Zhang et al, 2017 and Zheng et al, 2017). In the present paper, we describe a new species of the genus from Inner Mongolia, China. Type specimens are deposited in the Natural Museum of Hebei University, Baoding, Hebei, China.